A holistic approach to measure organizational readiness for knowledge management - Mohamed Razi, Mohamed Jalaldeen; Nor Shahriza, Abdul Karim; Ahmad Dahlan, Abdul Rahman; Mohamad Ali, Noor Azian (2016)
Management of organizational Knowledge is considered crucial in the present knowledge era. As a result, organizational readiness for knowledge management (KM) has been studied comprehensively from diverse viewpoints lately. KM enablers such as organizational culture, organizational structure and information technology infrastructures, and organizational members’ perception towards KM are assumed to be the predictors of KM readiness. Nevertheless, those dimensions could be part of KM readiness rather than just merely being its predictors considering the inevitable nature of those variables for KM implementation. Accordingly, the current study hypothesis that these factors with behavioral intention of organizational members form a holistic dimension of organizational readiness for KM. To verify this claim a questionnaire based survey was conducted among 313 executives in the Sri Lankan telecommunication industry. To validate the research instruments used a first order measurement model was formulated using AMOS version 16. Then, to test hypotheses a second order analysis was performed. The indices for model fit are good and the structural coefficients are significant showing the data fit to the model. Hence, the present work recommends that the KM enablers, organizational members’ perception and their behavioral intentions can be the dimensions of organizational readiness for KM